Mechanistic understanding of biogenic Mn-oxide mediated bisphenol A degradation - Shobnam, Nusrat (Kansas State University, 2019)
Bisphenol A (BPA) is a monomer of polycarbonate plastic which is produced in a large volume. The environmental fate of BPA has been of great concern due to its estrogenic properties. BPA had been considered recalcitrant under anoxic conditions, but recent studies showed that BPA is degraded by synthetic manganese oxides (MnO[subscript 2-syn]) without the requirement of oxygen. Manganese oxides (MnO₂) is a naturally occurring, strong oxidant, and its formation is mainly attributed to microbial Mn(II) oxidation in the environment. However, the reactivity of biologically produced MnO₂ (MnO[subscript 2-bio]) towards BPA has not been demonstrated. MnO[subscript 2-bio] is the result of microbial Mn(II) oxidation to Mn(IV). This process involves two single-electron transfer reactions with Mn(III) as a transient intermediate, and generally prevails in nature as Mn(III) containing Mn(III/IV)-oxide. Mn(III) is also a strong oxidant and can contribute to the oxidation reaction of BPA. In this thesis, we first used three well-characterized Mn(II) oxidizing bacteria (MOB), Roseobacter sp. AzwK-3b, Erythrobacter sp. SD-21, and Pseudomonas putida GB-1 to determine if they can mediate BPA degradation by producing MnO[subscript 2-bio]. Then, we examined the relative contribution of Mn(III) in BPA degradation by MnO[subscript 2-bio], using R. AzwK-3b as a model organism. In the first study, we demonstrated that R. AzwK-3b and E. SD-21 degraded BPA in absence of Mn(II) which has not been reported previously within these genera. In the presence of Mn(II), BPA degradation by the two strains became faster indicating MnO[subscript 2-bio] enhanced BPA degradation. P. putida GB-1 did not degrade BPA in the absence of Mn(II), but BPA degradation was observed in the presence of Mn(II). For all three bacteria, high BPA degradation rates were observed with 10 μM Mn(II) and BPA degradation decreased with increasing Mn(II) concentrations even though more MnO[subscript 2-bio] was formed with higher Mn(II) concentrations, suggesting that excess Mn(II) blocked the MnO[subscript 2-bio] surface. In the second study, we examined the relative role of Mn(III) in BPA degradation by MnO[subscript 2-bio]. MnO[subscript 2-bio] produced by R. AzwK-3b is a hexagonal-birnessite-like colloidal phase. This initial phase is known to undergo “aging” process and transforms into triclinic-birnessite-like particulate phase. We prepared two phases of MnO2-bio (colloidal and particulate) and their synthetic counterparts (hexagonal and triclinic birnessite) and compared Mn(III) content, Mn(III) availability, and their impacts on BPA degradation rates. At neutral pH, both phases of MnO[subscript 2-bio] did not show significant BPA degradation, but degradation occurred when a chelating agent, pyrophosphate, was added, suggesting that Mn(III) plays a major role in MnO[subscript 2-bio] reactivities. The result was consistent with the high Mn(III) content in colloidal and particulate MnO[subscript 2-bio] (64% and 62%, respectively). Relatively high Mn(III) content was observed in triclinic MnO[subscript 2-syn] (36%), but BPA degradation rate was not as high as MnO[subscript 2-bio]. We measured Mn(III) release rates of each MnO₂, and they showed high correlation with BPA degradation rates. Mn(III) release rates may account for accessible free Mn(III) from Mn(III)-pyrophosphate complex contributing to the higher BPA degradation rates. Combined, these results provide mechanistic understanding of Mn(III) containing Mn-oxides-mediated contaminant transformation that are relevant to natural and engineered environments.
Keywords: Biologically mediated abiotic degradation; Relative role; Mechanistic understanding